2015
DOI: 10.1039/c5ta01526j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the photocurrent of perovskite solar cells via modification of the TiO2/CH3NH3PbI3heterojunction interface with amino acid

Abstract: Novel modification of the TiO2/CH3NH3PbI3interface using glycine as a coupling agent induced higher coverage of perovskite through a two-step solution process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 23 publications
(46 reference statements)
1
63
0
Order By: Relevance
“…The fitted equivalent circuit model is composed of series resistance (R s ), two components for transfer resistance (R trans ) at the ETL/perovskite and the perovskite/HTL interfaces, and recombination resistance (R rec ) forming a parallel circuit with capacitors. The R trans is ascribed to high-frequency arc and the R rec is assigned to low-frequency arc [31,38,39]. Since the only difference among the three devices lies in the microstructure between TiO 2 mesoporous scaffold and FTO, we believe the difference of impedance spectra is in direct relevance to different charge transfer behaviors at the interface.…”
Section: Resultsmentioning
confidence: 95%
“…The fitted equivalent circuit model is composed of series resistance (R s ), two components for transfer resistance (R trans ) at the ETL/perovskite and the perovskite/HTL interfaces, and recombination resistance (R rec ) forming a parallel circuit with capacitors. The R trans is ascribed to high-frequency arc and the R rec is assigned to low-frequency arc [31,38,39]. Since the only difference among the three devices lies in the microstructure between TiO 2 mesoporous scaffold and FTO, we believe the difference of impedance spectra is in direct relevance to different charge transfer behaviors at the interface.…”
Section: Resultsmentioning
confidence: 95%
“…It was reported that a modification of the interface between ZnO and perovskite layer using self-assembled monolayer can optimize the morphology of perovskite layer and improve the performance of PSCs [23, 24]. It was also demonstrated that modifying the TiO 2 /CH 3 NH 3 PbI 3 heterojunction interface by glycine can enhance the photovoltaic performance of two-step solution-processed PSCs [25]. …”
Section: Introductionmentioning
confidence: 99%
“…This increase of the efficiency was explained by the retardation of charge recombination, and better perovskite crystal growth. Some other organic monolayers were used to modify the surface of scaffold through the influence of the morphology and growth of perovskite, such as glycine, thiols and 4-aminobenzoic acid, yielding positive effects on cell performance [75][76][77]. A summary of the published representative results of MPSCs' performance parameters with different scaffold interface modification is listed in Table 2.…”
Section: Scaffold Interface Engineeringmentioning
confidence: 99%